The Correlation between Noise in Workplace and Sleep Quality in Workers at PT. Muroco Jember Wood Processing Factory - Lathifa Rusyda Gani; Dwita Aryadina Rachmawati; Laksmi Indreswari; Alif Mardijana; Yudha Nurdian (Journal of Agromedicine and Medical Sciences, 2018)
Noise is a problem that can’t be resolved properly until now because it is one of the factors that sometimes is neglected from the work environment, so it can be a serious threat to the health of workers. The production tools and engines in the factory as the result of technology development produce a sound that can cause noise and interfere with health. Noise can also cause a variety of other disorders such as physiological, psychological, and communication disorders. Psychological disorders can include discomfort, lack of concentration, insomnia, and irritability. Sleep disorders can be associated with 13% of occupational hazards. Workers who have sleep disorders have a 1.62 times higher risk of experiencing work accidents compared with workers who do not have sleep disorders. The aim of this study is to determine the correlation between noise in workplace and sleep quality in workers at PT. Muroco Jember wood processing factory. This is an analytical observational study with cross sectional study design using workers of the factory who meet inclusion and exclusion criteria. Noise in the workplace was measured with sound level meter and sleep quality of the workers was measured with Pittsburgh Sleep Quality Index Questionnaire. Spearman correlation test result between these variables is p= 0,899. That result indicates that there is no significant correlation between noise in workplace and sleep quality in workers at PT. Muroco Jember wood processing factory. Keywords: Noise, Sleep Quality, Worker